THE STUDI ETNOBOTANI TUMBUHAN OBAT TRADISIONAL PENGOBATAN HIPERTENSI MASYARAKAT DESA HALLAPADJI KECAMATAN SABU LIAE KABUPATEN SABU RAIJUA : ETHNOBOTANICAL STUDY OF TRADITIONAL MEDICINAL PLANTS FOR HYPERTENSION TREATMENT IN THE COMMUNITY OF HALLAPADJI VILLAGE, SABU LIAE DISTRICT, SABU RAIJUA REGENCY - Mariana Lulu Bale, Rince; Iramaya Dilak, Hory; Pietherson Eryah, Henry (Jurnal Biogenerasi, 2025)
This study aims to identify the types of traditional medicinal plants used by the community of Hallapadji Village, Sabu Liae District, Sabu Raijua Regency, Eats Nusa Tenggara Province, in the treatment of hypertension, including the plant organs utilized, methods of use, and processing techniques. The research was conducted from June to July 2025 using a qualitative descriptive method through observation, structured interviews, documentation, and the preparation of herbarium specimens, involving 30 respondents consisting of 5 key informants (traditional healers) and 25 non-key informants selected through snowball sampling. The findings revealed 29 species of medicinal plants from 20 families. The dominant family was Zingiberacea represented by ginger (Zingiber officinale R.), kencur (Kaempferia galanga), and turmeric (Curcuma longa), the Asteraceae family included white bush (Chromolaena odorata), african leaf (Vernonia amygdalina), and beluntas (Pluchea indica), the Cucurbitaceae family comprised bitter gourd (Momordica charantia L.), chayote (Sechium edule), and cucumber (Cucumis sativus). The Lamiaceae, Acanthaceae, and Meliaceae by two species (6.90%). Leaves were the most frequently used organ (61.11%), followed by fruits (16.67%), rhizomes (8.33%), flowers (5.56%), and tubers, stem, and shoots, each with (2.78%). The community applied two main utilization methods drinking herbal decoctions (83.76%) and consuming raw plant parts such as fruits (16.67%), while processing techniques included boiling (36.36%), soaking (33.33%), pounding (15.15%), and direct consumption (15.15%).